2021
DOI: 10.3390/ma14216607
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Grown Carbon Nanotubes Reinforced Pyrocarbon Matrix in C/C Composites with Improved Mechanical Properties

Abstract: In order to achieve the highly efficient preparation of high-performance carbon/carbon (C/C) composites, epitaxial grown carbon nanotubes (CNTs) and a pyrocarbon matrix were simultaneously synthesized to fabricate CNT-reinforced C/C composites (CC/C composites). With precise control of the temperature gradient, CNTs and the pyrocarbon matrix could grow synchronously within a 2D needle-punched carbon fiber preform. Surprisingly, the CNTs remained intact within the pyrocarbon matrix at the nano-level, and the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In addition, some new CVD methods are also proposed, such as chemical liquid-vapor infiltration (CLVI) [74][75][76][77] and thermal gradient chemical vapor infiltration (TGCVI). [44,46,78,79] From the point of view of reducing the reaction temperature, many new preparation methods making full use of plasma, laser, electron beam, and other auxiliary methods have been proposed to fabricate 1D nanomaterials, which would have a very big application potential in nanomaterials reinforced C/C composites.…”
Section: Chemical Growth Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, some new CVD methods are also proposed, such as chemical liquid-vapor infiltration (CLVI) [74][75][76][77] and thermal gradient chemical vapor infiltration (TGCVI). [44,46,78,79] From the point of view of reducing the reaction temperature, many new preparation methods making full use of plasma, laser, electron beam, and other auxiliary methods have been proposed to fabricate 1D nanomaterials, which would have a very big application potential in nanomaterials reinforced C/C composites.…”
Section: Chemical Growth Methodsmentioning
confidence: 99%
“…achieve the efficient preparation of 1D nanomaterials reinforced C/C composites. Kou et al reported a novel catalyst-assisted thermal gradient CVI (TGCVI) method (Figure 3c), [44,46] which realize the growth of CNTs and the deposition of PyC matrix simultaneously when precisely controlling the temperature gradient. In addition, Xu et al [45] found that CNTs and ZrB 2 were in situ prepared at same time during the thermal pyrolysis of zirconium (Zr) and boron (B)-contained polymeric precursors, forming the CNTs reinforced ZrB 2 modified C/C composites in one step (Figure 3d).…”
Section: "One-step" Fabrication Processmentioning
confidence: 99%
See 3 more Smart Citations